A közigazgatás és ügyfél kapcsolatának fejlődése röviden : Ügyfelet megillető jogok megjelenése és változása a hazai hatósági ügyintézés során (Evolution of the relationship between public administration and the client in brief : Emergence and evolution of customer rights in domestic public administration) - Ferenc Varga (KözigazgatásTudomány)
In this article I will attempt to give a brief overview of the relationship between administration and the client. With the emergence of communities, there naturally appeared a range of issues that affected the whole of society and whose effective resolution was felt to be the responsibility of all. The initial hierarchical systems, concentrated in a single hand, were able to achieve relatively spectacular results, which were relaxed in early feudalism, with the emergence of individual small (mainly feudal) communities and the disintegration of large empires. The early, more disorganised forms of administration were replaced by a more organised bureaucratic system based on a division of labour based on expertise, with the emergence of monarchies in the 18th century. In the continental legal order, the emergence of chamber law, administrative law as a separate branch of law, and while Anglo-Saxons’ system, the development of a patronage system, the world wars everywhere showed that effective management can only be achieved through an administration based on organisation and performance. The theories underpinning these efforts, in the domestic administration, typically received or followed, did not emerge until the 20th century, although the Prussian organisation of the state could have been typical from the 16th century. The changes in administrative systems have also naturally shaped the status of the subjects - from subject to citizen, and then to citizen, at the mercy of laissez faire economic policies, to equal client of the service administration.